Frequency of Tuberculosis and its Outcomes After Anti-Tuberculosis Treatment According to Age and Gender - Jai Dev Maheshwari, Shabana Qabulio, Mukesh Kumar, Ali Nawaz Bijarani, Jai Kirshin Ambwani, Damni Advani (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of pulmonary tuberculosis and its outcomes after anti-tuberculosis treatment according to age and gender. Methods: This cross-sectional study was conducted at the department of Microbiology, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre Karachi, with the collaboration of different DOTs centers and chest ward JPMC, Karachi Medical and Dental College, Karachi. All newly diagnosed pulmonary tuberculosis patients who registered for treatment, of either gender, were included. All the patients were followed until the end of the treatment, and they were assessed regarding treatment outcomes in terms of the success and failure of the treatment according to the age and gender of the patients. A self-made proforma was structured to collect the information, and SPSS version 26 was used for the purpose of data analysis. Results: A total of 237 cases were observed, their mean age was 41.80+16.44 years and their mean weight was 51.09+7.90 kg. Males were in majority 84.0% and females were 16.0%. The majority of cases (96.2%) had completed treatment, while 3.8% of cases had not yet completed treatment.91.0% of the patients were cured, while the remaining 8.40% were still not cured during the study period. Treatment outcome was statistically significant according to age (p = 0.001), while statistically insignificant according to gender (p = 895). Conclusion: As per the study conclusion, the frequency of pulmonary tuberculosis was frequently higher among males compared to females. Treatment outcome was influenced by age greater than 60 years, while no gender effects were observed. Keywords: Tuberculosis, age, gender, treatment